2017
DOI: 10.3389/fpls.2017.01910
|View full text |Cite
|
Sign up to set email alerts
|

Accession-Dependent CBF Gene Deletion by CRISPR/Cas System in Arabidopsis

Abstract: The CRISPR/Cas system became a powerful genome editing tool for basic plant research and crop improvement. Thus far, CRISPR/Cas has been applied to many plants, including Arabidopsis, rice and other crop plants. It has been reported that CRISPR/Cas efficiency is generally high in many plants. In this study, we compared the genome editing efficiency of CRISPR/Cas in three different Arabidopsis accessions [Col-0, Ler, and C24RDLUC (C24 accession harboring the stress-responsive RD29A promoter-driven luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
11
0
3
Order By: Relevance
“…After 2 min of centrifugation at 16,000 × g , the supernatant was transferred to a siliconized tube, and 10 μL of the appropriate antibody was added. Antibodies used were anti-AcH3 (Millipore), antiacetylated H3K9/K14 (Upstate Biotechnology), anti-HOS15 ( 66 ), anti-CBFs ( 70 ), and anti-HD2C (Agrisera). After incubation overnight with rotation at 4 °C, 60 μL SS DNA/Protein A agarose was added and incubation continued for 2 h. The agarose beads were then washed with 1 mL of each of the following: two times lysis buffer, one time LNDET buffer [0.25 M LiCl, 1% Nonidet P-40, 1% deoxycholate, 1 mM EDTA, 10 mM Tris (pH 8)], and three times TE buffer [10 mM Tris⋅HCl (pH 8), 1 mM EDTA].…”
Section: Methodsmentioning
confidence: 99%
“…After 2 min of centrifugation at 16,000 × g , the supernatant was transferred to a siliconized tube, and 10 μL of the appropriate antibody was added. Antibodies used were anti-AcH3 (Millipore), antiacetylated H3K9/K14 (Upstate Biotechnology), anti-HOS15 ( 66 ), anti-CBFs ( 70 ), and anti-HD2C (Agrisera). After incubation overnight with rotation at 4 °C, 60 μL SS DNA/Protein A agarose was added and incubation continued for 2 h. The agarose beads were then washed with 1 mL of each of the following: two times lysis buffer, one time LNDET buffer [0.25 M LiCl, 1% Nonidet P-40, 1% deoxycholate, 1 mM EDTA, 10 mM Tris (pH 8)], and three times TE buffer [10 mM Tris⋅HCl (pH 8), 1 mM EDTA].…”
Section: Methodsmentioning
confidence: 99%
“…The first three members of this family are closely located in less than 8 Kb in chromosome 4 (Fig 1A), making extremely difficult to obtain a triple mutant by classical crossing strategy. This has been recently achieved by CRISPR/Cas9-induced mutagenesis [23] using two sgRNAs that the authors selected by manual evaluation of sequence alignments, manual selection of candidates, and specificity verification with CRISPR-P [1]. I used the A. thaliana genomic coding sequences (TAIR v10) of the four CBF genes as a multiple query in ARES-GT, to search for candidate sgRNAs using both Cas9 and Cas12a.…”
Section: Design Of Guide Rna Matching Multiple Cbf Genesmentioning
confidence: 99%
“…The first three members of this family are closely located in less than 8 Kb in chromosome 4 ( Figure 1A), making extremely difficult to obtain a triple mutant by classical crossing strategy. This has been recently achieved by CRISPR/Cas9-induced mutagenesis (Cho et al, 2017) using two sgRNAs that the authors selected by manual evaluation of sequence alignments, manual selection of candidates, and specificity verification with CRISPR-P (Lei et al, 2014). I used the A. thaliana genomic coding sequences (TAIR v10) of the four CBF genes as a multiple query in ARES-GT, to search for candidate sgRNAs using both Cas9 and Cas12a.…”
Section: Design Of Guide Rna Matching Multiple Cbf Genesmentioning
confidence: 99%
“…In total, 10 Cas9 and 5 Cas12a candidates were identified that match more than one CBF gene and did not present any offtarget outside CBF genes ( Figure 1B, 1C). Among them were included the two sequences previously reported (Cho et al, 2017), corresponding to Cas9CBF1_015 and Cas9CBF2_124 in this work.…”
Section: Design Of Guide Rna Matching Multiple Cbf Genesmentioning
confidence: 99%
See 1 more Smart Citation